KEPATUHAN WAJIB PAJAK PBB-P2: PENGARUH TARIF, PEMAHAMAN, DAN PENDAPATAN - Putri, Rani Cahya; Indriyani, Rinni; Sari, Fitriya (Jurnal Riset Akuntansi Politala, 2025)
Compliance with Cirebon’s Land and Building Tax (PBB-P2) is the focus of this analysis, which aims to examine the connection between taxpayer income, tax knowledge, and tax rates. Low compliance with paying PBB-P2 and increases to tax rates in 2024 form the basis of this research. Obtained the information for this research through questionnaires, utilizing a quantitative approach. Besides conducted data validity checks, hypothesis testing, and classical assumption tests, but also employed the method of multiple linear regression. Tax knowledge and taxpayer income affect their compliance with the Land and Building Tax (PBB-P2). The result shows that tax knowledge and taxpayer income have a greater impact on tax compliance than tax rates.